Design of road humps in residential area / Muhammad Akram Adrian, Teoh Sian Hoon and Lim Boon Tik - Adrian, Muhammad Akram; Teoh, Sian Hoon; Lim, Boon Tik (Universiti Teknologi MARA, Pulau Pinang & and Pusat Penerbitan Universiti (UPENA), 2005)
Speed hump is one of the traffic calming devices that has been installed in residential area in Malaysia. This study was to find a better design of speed hump in reducing speed of vehicles. Data were collected using Speed Radar Meter Detector. Two sets of data were collected. They were speed before reaching the hump (at 30m before the device, this is due to safe stopping sight distance) and speed over the hump for both motorcycles and cars. Data were collected in one hour or at least 50 vehicles at three locations. The effectiveness of the humps is measured by comparing the reduction in speed at the hump. The effectiveness of the speed hump also influenced by other parameters such as height and width of it.